Optimizing Civic Education as Legal Awareness Education of ITE Law as an Effort to Improve Social Media Ethics of Students of SMA Negeri 1 Amlapura - Putra, I Kadek Agus Juniartana; Budiarta, I Wayan; Sanjaya, Dewa Bagus; Dinata, I Putu Agus Hendra; Satriawan, Komang Deta Ary; Pramaputra, I Gusti Agung Ngurah Satria Dwi; Pramana, Gede Bayu Byana; Viriya, Arrya Karuna (Jurnal Pendidikan Kewarganegaraan Undiksha, 2025)
The rapid development of the digital era has created new challenges in civic education, particularly in building students' legal awareness regarding the use of information and communication technology. This study aims to examine how Civic Education can be optimized as a means of legal awareness education for the Electronic Information and Transaction Law at SMA Negeri 1 Amlapura. This research employs a qualitative descriptive research method with a literature study approach. Data collection techniques were conducted through interviews with Civics teachers, participatory observation, and document analysis, then analyzed using qualitative description. The research results indicate that the implementation of Civic Education optimization requires fundamental reconstruction from conventional learning methods toward approaches that are responsive to digital technology dynamics. The main challenges are the limited understanding of teachers in integrating legal materials contextually, inadequate facilities and infrastructure, and the characteristics of digital generation students with short attention spans. Analysis shows that the majority of students use social media platforms very intensively but do not understand the provisions in the Electronic Information and Transaction Law. Comprehensive solutions offered include integration of legal materials in the Civic Education curriculum, implementation of contextual learning methods through judicial simulation and collaboration with law enforcement agencies, utilization of technology in educational media, and continuous evaluation of civic education teacher competencies.